Peptidi v kozmetiki - smotrnost njihove uporabe - Bjelošević, Maja (Farmacevtski vestnik, 2019)
Nowadays, cosmetology and cosmetic products are one of the fastest-growing scientific areas, increasingly focused towards individuals' needs and preferences. Thus, we are facing with new trends that include cosmetic products with added value plus a zero-waste mentality which is changing current consumers' habits. Cosmetic products based on biological macromolecules, including peptides, can indisputably be enclosed within this field, representing the scope of this article. In the following review, new trends in the field of cosmetic products with incorporated peptides as cosmetically active ingredients are pointed out. moreover, benefits as well as challenges in terms of development and efficiency of such products are critically depicted. Throughout the contribution, authors want to answer the question regarding relevance of using peptides in the active care as well as their effects on the skin surface.
Keywords: aktivna nega kože; bioaktivni peptidi; Kozmetični izdelki; Kozmetika; Peptidi; proteini sirotke; tridelnost narave; učinkovitost kozmetičnih izdelkov; vegetabilizirane kovine